Laparoscopic excision for ectopic peritoneal paragonimiasis mimicking a gastric duplication cyst: A case report. (September 2021) - Roh, Chul Kyu; Jung, Min Jung
Abstract: Introduction: Paragonimiasis, lung fluke disease caused by infection with Paragonimus species, is a food-borne parasitic zoonosis. The overriding symptoms of Paragonimus westermani infection include chronic cough, shortness of breath, and pleuritic pain. Extrapulmonary paragonimiasis caused by aberrant parasitic migration is known to occur in a variety of sites such as the brain, abdominal wall, and intraperitoneal cavity. Ectopic paragonimiasis is an uncommon disease that presents with a few clinical manifestations, which makes it difficult to diagnose and treat. Case presentation: A 47-year-old man with an unremarkable medical and surgical history presented with a peritoneal lesion that was discovered incidentally on abdominal computed tomography during routine health screening. The patient did not exhibit any associated symptoms such as abdominal pain. The radiologic diagnosis was a gastric duplication cyst and we performed laparoscopic excision of the peritoneal mass. Histopathological examination revealed paragonimiasis, and the result of the skin test for paragonimiasis was positive. The patient was treated with praziquantel. Clinical discussion: The diagnosis of ectopic peritoneal paragonimiasis remains challenging due to inexperience, misdiagnosis, and its rarity. Clinicians should bear in mind that an intra-abdominal mass may be related to a parasitic infection. The detection of the ova of Paragonimus parasites in sputum and biopsy specimens may be difficult due to an insufficient amount. Conclusion: Clinicians need to thoroughly take the patient's history and clinically suspect parasitic infections. Laparoscopic resection of this rare mass is safe, feasible, and allows for rapid recovery. Highlight: Ectopic paragonimiasis is a rare disease with a few clinical symptoms. The rarity of ectopic paragonimiasis makes it difficult to diagnose and treat. Clinicians should suspect parasitic infections. The laparoscopic approach could be a treatment option for abdominal masses.